A contribution to the understanding of the ethology of the cichlids of Southern Africa - Ribbink, Anthony J (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1975)
Allopatric populations of Pseudocrenilabrus philander were found to differ in male breeding coloration. These colours are described and attention is drawn to the possibility that male coloration might prevent population hybridisation. Behaviour of the allopatric populations was studied in the laboratory. The execution of behaviour patterns of the various populations was found to be indistinguishable, and very similar to that of Haplochromis. Behaviour of P. philander was recorded in three morphologically different natural water bodies. Diurnal activities were found to follow a set rhythm. Though P. philander was shown to have adapted to a variety of habitats they retained their behavioural Components in an unchanged form. Field and laboratory observations are used to propose a behavioural mechanism for the natural regulation of population density. Although aggression between conspecific territorial Sarot herodon mossambicus habituated so that neighbours could live close to one another, it was found that P.philander are intolerant of their neighbours and are consequently forced apart. Though the execution of behaviour patterns was apparently identical for all populations of P. philander, field observations indicated that the frequency of performance differed. An experimental procedure was established to quantitatively compare the behaviour of various populations. As a result of comparative and choice chamber investigations, it is suggested that one of the four populations of P. philander would be unlikely to hybridise with the others if they were to become sympatric. These popUlations would be kept apart because of colour and behavioural differences. Differences of egg-size, fry-size, developmental and interbrood periods were also found, providing further evidence of incipient speciation. Evolutionary divergence of the allopatric populations of P. philander is discussed against a background of geological and geographical evidence. Consideration is given to the role of male coloration, ethological barriers and the importance of ethological differences to taxonomy. Behavioural evidence suggests that P. philander has closer affinities with the haplochromids than was initially realised. It is concluded that the clinal populations of P. philander should not be taxonomically separated, and it is argued that it would be premature to give the Kuruman population an elevated taxonomic status.
Keywords: Cichlids -- Africa, Southern; Fishes -- Africa, Southern